2013
DOI: 10.1136/bmjopen-2013-003442
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of recovery among homeless adults with mental illness who participated in a randomised controlled trial of Housing First: a longitudinal, narrative analysis

Abstract: ObjectivesThis study used longitudinal, narrative data to identify trajectories of recovery among homeless adults with mental illness alongside the factors that contribute to positive, negative, mixed or neutral trajectories over time. We expected that participants who received Housing First (HF) would describe more positive trajectories of recovery than those who were assigned to Treatment as Usual (TAU; no housing or support provided through the study).DesignNarrative interview data were collected from parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 39 publications
0
39
1
1
Order By: Relevance
“…Qualitative analyses identified substantial deficiencies in shelter and support services in TAU [42]. Notwithstanding these previous findings, the current results indicate that neither CHF or SHF were sufficient to mediate changes over 24 months in measures of quality of life, overall health, or psychiatric symptom severity, beyond what would be expected from prolonged homelessness with minimal supports.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Qualitative analyses identified substantial deficiencies in shelter and support services in TAU [42]. Notwithstanding these previous findings, the current results indicate that neither CHF or SHF were sufficient to mediate changes over 24 months in measures of quality of life, overall health, or psychiatric symptom severity, beyond what would be expected from prolonged homelessness with minimal supports.…”
Section: Discussioncontrasting
confidence: 58%
“…Additional factors that may have contributed to improvement in CHF were on-site recreational and vocational opportunities, and a supportive peer environment. Qualitative research has found that ongoing substance use and experiences of loneliness and isolation are often reported following the transition to SHF [40–42]. Difficulties transitioning to SHF may explain some of the null findings compared with TAU over 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of previous studies (all of them qualitative) have attempted to understand recovery (mental health and/or substance abuse) from the perspective of those engaged in Housing First programming. Three of these studies targeting Housing First clients with mental illness have demonstrated how participants viewed housing as an essential foundation for recovery because of its ability to foster hope and stable social relationships (Kirst et al 2014; Patterson et al 2013; Polvere et al 2013). Cabassa et al (2013) recruited individuals with co-occurring disorder from a Housing First program in order to better understand the recovery process through the Photovoice method.…”
Section: Housing First: Study Setting For Co-occurring Disorder Recoverymentioning
confidence: 99%
“…Thus, it does not follow the original scatter-site version of the housing-first philosophy. 19 Early studies of housing-first approaches have shown that they improve housing stability, 20,21 decrease criminal activity and jail bookings, [22][23][24] improve recovery trajectories for those struggling with mental illness, 25 and even help reduce substance use. [26][27][28] One study also found a potential reduction in acute care medical costs associated with housing first practices.…”
Section: Introductionmentioning
confidence: 99%